Righting a Wrong: A Discussion of "The Poetics of Boundary Violation: Anne Sexton and Her Psychiatrist". Issue 2 (3rd March 2020) - Celenza, Andrea
Abstract : This commentary addresses several issues raised in Charles Levin and Dawn Skorczewski's probing and insightful paper (this issue) on the tragic story of Anne Sexton's sexual relations with her analyst. Highlighted are (1) the nature of the betrayal in sexual boundary violations, that being the lie ; (2) the false dichotomy of real and unreal analytic love; and (3) the ways in which Sexton attempted to be heard, even through unconscious emanations, as in her poetry. Speculative inquiry is offered about Duhl and others involved in her tragic story. Finally, and in accord with Levin and Skorczewski's rendering, I aim to celebrate Sexton and her poetry, returning her voice to her in both conscious and unconscious expressions. Atonement and repair are offered in truth-telling – a righting of her legacy that hopefully will be helpful to others as well.